World Politics: University in Networks of Contemporary World - I. I. Zhukovskiy (Vestnik MGIMO-Universiteta)
World politics of a present-day demands a very specific combination of usage of the traditional foreign policy’s instruments as well as “new ones”. Universities as well as international science & education networks play an important role in providing support of the foreign policy’s initiatives of the global or regional dimension.